Light intensity as major factor to maximize biomass and lipid productivity of Ettlia sp. in CO2-controlled photoautotrophic chemostat. (November 2017) - Seo, Seong-Hyun; Ha, Ji-San; Yoo, Chan; Srivastava, Ankita; Ahn, Chi-Yong; Cho, Dae-Hyun; La, Hyun-Joon; Han, Myung-Soo; Oh, Hee-Mock
Highlights: Biomass productivity of Ettlia sp. was maximized using CO2 -controlled chemostats. Highest biomass productivity of 1.48 g L −1 d −1 at 1500 μmol photons m −2 s −1 . Lipid content was around 19.8% regardless of pH and light intensity variation. Light intensity was the key factor for high biomass productivity. Abstract: The optimal culture conditions are critical factors for high microalgal biomass and lipid productivity. To optimize the photoautotrophic culture conditions, combination of the pH (regulated by CO2 supply), dilution rate, and light intensity was systematically investigated for Ettlia sp. YC001 cultivation in a chemostat during 143 days. The biomass productivity increased with the increase in dilution rate and light intensity, but decreased with increasing pH. The average lipid content was 19.8% and statistically non-variable among the tested conditions. The highest biomass and lipid productivities were 1.48 g L −1 d −1 and 291.4 mg L −1 d −1 with a pH of 6.5, dilution rate of 0.78 d −1, and light intensity of 1500 μmol photons m −2 s −1 . With a sufficient supply of CO2 and nutrients, the light intensity was the main determinant of the photosynthetic rate. Therefore, the surface-to-volume ratio of a photobioreactor should enable efficient light distribution to enhance microalgal growth.